(untitled) (Asian Education Studies, 2019)
A systematic survey on the life-style of college undergraduate dormitory of a local public university finds that, most of the time, undergraduates “amuse themselves” in the dorms and mutual learning and communication time is relatively insufficient. Students in the dorms have a higher expectation on interpersonal relationship. However, in reality, there exists the problem that the affection between them is indifferent. Besides, when they come into conflicts, they are incapable of resolving the conflicts through a normal channel. Furthermore, students are relatively satisfied with the life service in dormitory management, while they are not satisfied with the hardware facilities and the rules and regulations. To improve the management level of college student dormitory and promote development of students, it is necessary for the department of college dormitory management to strengthen construction of the physical environment, develop an organic dormitory interpersonal network and establish the dormitory organizational structure and institutional norms in which students can participate. Above all, the department of dormitory management needs to establish the system of dormitory education to help students carry out effective education in life.